Access to N-Acetylated Chitohexaose with Well-Defined Degrees of Acetylation. (5th June 2017) - Li, Kecheng; Xing, Ronge; Liu, Song; Qin, Yukun; Li, Pengcheng
Abstract : Chitohexaose has attracted wide interest due to its special bioactivities and these potential activities are significantly related to N-acetylation. Herein, six chitohexaose fractions with different degrees of acetylation were prepared by selective N-acetylation and ion-exchange chromatography and further analyzed by ESI/MS. It is revealed that all the six N-acetylated chitohexaoses were of single molecular weight, the molecular weights of which were exactly assigned to 1026.44 Da, 1068.44 Da, 1110.48 Da, 1152.48 Da, 1194.49 Da, and 1236.48 Da, respectively. These results suggested that the six prepared N-acetylated chitohexaoses were N-acetylchitohexaose (D5A1), di-N -acetylchitohexaose (D4A2), tri-N -acetylchitohexaose (D3A3), tetra-N -acetylchitohexaose (D2A4), penta-N -acetylchitohexaose (D1A5), and hexa-N -acetylchitohexaose (A6), respectively, which are of great significance to screen their bioactivities and discover well-defined chitooligosaccharide molecules as potential drugs.